Standardization of Information Disclosure in Non-Financial Reporting of Commercial Organizations - I. V. Alekseeva; E. S. Popova (Учёт. Анализ. Аудит, 2022)
The paper describes the problem of standardization of the formation of non-financial reporting of Russian commercial organizations, since the information requests of stakeholders are growing, in connection with this, commercial organizations are facing the problem of optimal disclosure of information about all aspects of their activities. The aim of the study is to analyze international standards and modern trends for the disclosure of non-financial in the standardization of information disclosure in reporting of Russian domestic companies and the possibility of their application for its formation. The methodological base of the study includes fundamental concepts and approaches, fundamental provisions of economic science and applied developments, substantiated by the works of foreign and domestic scientists in the field of non-financial reporting. The authors reviewed various approaches to understanding the materiality of reporting in terms of the amount of information covered by its various types. In the work’s course, the authors studied the existing international standards used by all commercial organizations in the preparation of their reports on sustainable development (using the GRI standards), as well as they proposed a critical analysis of the GRI and SASB standards and the content of the integrated report. Also, the reaserch highlited the features of GRI, SASB and IIRC. The theoretical and practical significance of the study lies in the generated recommendations for the standardization of non-financial reporting for Russian commercial organizations.